Serum Sickness following Tetanus Toxoid Injection - Saja alhawal; Manar Aldarwish; Zainab Almoosa (Hindawi Limited, 2021)
Serum sickness is an allergic reaction that frequently occurs in patients after the injection of foreign protein or serum. It is characterized by fever, skin rash, enlarged lymph nodes, and painful joints. In this case, we describe a case of 6-year-old girl who developed a rash and arthralgia after being vaccinated with tetanus toxoid injection after a cut wound.